1991
DOI: 10.1017/s0003356100020110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of litter size on herbage intake at pasture by ewes and their progeny

Abstract: 1991). Effect of litter size on herbage intake at pasture by ewes and their progeny. AbstractThirty-four mature ewes (17 rearing twins and 17 rearing singles) were used to examine the effect of litter size on herbage intake at pasture by ewes over the course of lactation; intake by their lambs during weeks 13 to 15 of lactation was also evaluated. Daily organic matter intake (OMI) was estimated using the n-alkane technique. Ewes and lambs rotationally grazed 19 X 0-15-ha paddocks during the experimental period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Ewe breed cross had no effect on OMI. Vulich et al (1990) found that adult ewes from breeds of a large mature size had higher intake per unit of body weight than ewes from breeds of a small mature size. There are, however, relatively few measurements on the effect of ewe breed on herbage intake at pasture.…”
Section: Animal Intakementioning
confidence: 90%
“…Ewe breed cross had no effect on OMI. Vulich et al (1990) found that adult ewes from breeds of a large mature size had higher intake per unit of body weight than ewes from breeds of a small mature size. There are, however, relatively few measurements on the effect of ewe breed on herbage intake at pasture.…”
Section: Animal Intakementioning
confidence: 90%
“…Yb was determined using atomic absorption spectrophotometry with a nitrous oxide/acetylene flame (Varian spectraa-20, Varian France SA, Les Ulis, France) after calcination and digestion in nitric acid (94.5 g/l) as described by Siddons et al (1985). N-alkane concentrations in the feed and faeces were determined using gas chromatography according to Mayes et al (1986) after direct saponification (Vulich et al, 1991).…”
Section: Chemical Analysesmentioning
confidence: 99%
“…The decline in herbage DM yield of 54.2 kg/ha per day delay in grazing after early December has a significant impact on spring grass availability. Using the data of Vulich et al (1991), a decline of 54.2 kg DM/ha is equivalent to 20 grazing days for ewes rearing twin lambs from birth to weaning. However, whilst delaying grazing reduced herbage yield, it increased feed value as indicated by ME concentration due to a reduction in fibre concentration, but did not impact water-soluble carbohydrate or CP concentrations.…”
Section: Keady and Hanrahanmentioning
confidence: 99%